Cognition and Transfer of Contagious Substance in Hindu Himalayan Pilgrim Journeys - Nordin, Andreas (Open theology, 2016)
Ideas and practices about the transfer of substances believed to be charged with positive or negative properties are significant features of pilgrimages. Oftenneglected features of pilgrimages can be addressed by adopting concepts from the Cognitive Science of Religion. Religious pilgrimages are popular phenomena that are based on ritual interaction with culturally-postulated counterintuitive supernatural agents. This article partly refers to and analyses ethnographic data gathered during fieldwork among Hindu pilgrims in Nepal and Tibet. The pilgrims received items to take home from the pilgrimage site but they also left other items there. This constituted a transfer of contagious substances that carried blessings and supernatural agency/power and it enabled the discharging of defilement, sin or evil. The aim of this article is to show how the beliefs about substance transfer are shaped by cultural institutions and by cognitive selection pressures related to psychological essentialism and concepts of agency and contagion relating to counterintuitive agents.